Examining story production improving creative thinking in the alpha generation: A systematic review - Villacorta Castro, Griselda Jacqueline (2025)
Purpose: The present systematic review study had the general objective of analyzing and synthesizing the existing scientific evidence on the effectiveness of the production of stories to improve creativity in the alpha generation. Methodology: The PRISMA 2020 method was used to develop a systematic review where the databases used were Scopus, ScienceDirect, Web of Science and university repositories, with the search strategy ("production of stories") AND ("creativity" OR "creative thinking") AND ("primary education") in Spanish and English. After applying the inclusion and exclusion criteria, 10 articles containing a total of 1088 sample elements were obtained. Findings: The works were mainly of a quasi-experimental design, using story production programs as an independent variable, and in the last two years adding digital and audiovisual resources. No standardized instrument was found for the evaluation of creativity. Implications to Research and Practice: sIn the experimental design studies, the positive influence of the production of stories on creativity in primary school students of the alpha generation was demonstrated, in the correlational studies a moderate and significant relationship was evidenced. It is striking that, contrary to what is suggested by specialists, the number of sessions reported is less than those recommended without losing effectiveness.